Significance of magnetic resonance imaging for early rheumatoid arthritis activity - E Y Pogozeva (Научно-практическая ревматология, 2009)
Objective. To assess possibility of magnetic resonance image (MRI) application for rheu- matoid arthritis (RA) activity and severity assessment.Material and methods. 100 pts with RA who fulfilled the 1987 ACR criteria with disease duration less than 12 months were included. Standard clinical examination with evaluation of tender and swollen joint counts, acute phase markers, hand and foot X-ray and hand MRI with 0,2 T Artoscan apparatus (ESAOTE Biomedica, Italy) were performed.Results. MRI showed hand joint synovitis in 94,5%, erosions – in 67,3% of cases. X-ray examination revealed erosions in only 20,8% of pts. Localization of erosions revealed by X-ray and MRI coincided in 36,4% of cases and in 61,8% of pts erosions were detected only by MRI. MRI confirmed clinical conclusion about presence or absence of metacarpophalangeal and wrist joint synovitis in 64,5% and 74,5% of cases respectively. In8,2% and 21,8% MRI revealed signs of synovitis in clinically intact joints. MRI synovitis score correlated with clinical and laboratory measures of disease activity – DAS 28 (r=0,37, p=0,001), CRP(r=0,30, p=0,001), ESR (r=0,42, p=0,001), HAQ (r=0,24, p=0,001). Weak correlation was revealed between ESR and presence of erosions (r=0,29), CRP, ESR and MRI signs of bone marrow edema (r=0,27, p=0,005 and r=0,29, p=0,002 respectively). Relationship between laboratory and clinical features was weaker and referred only to CRP level and swollen joint count (p=0,05).Conclusion. MRI signs may be used as additional and independent measures of inflammatory activity (particularly synovitis score) and severity of RA